Data Analysis on Human Resource Management and Development of Village-Owned Enterprises in Improving the Welfare of the Paspan Village Community in Banyuwangi Regency - I Gede Wirayasa; Ida Ayu Putu Widani Sugianingrat; I Putu Putra Astawa; Lilik Khomsatin Romadhoni (SEAN Institute, 2026)
Village-Owned Enterprises (BUM Desa) are a strategic instrument in driving village economic development through the management of local potential and community empowerment. The success of BUM Desa is not only determined by the organizational governance aspect, but also by the ability to develop human resources as the main asset of village development. This study aims to analyze the governance and human resource development carried out by BUM Desa Jaya Makmur in improving the welfare of the community of Paspan Village, Glagah District, Banyuwangi Regency. The study used a qualitative approach with a case study method. Data were obtained through in-depth interviews, observation, and documentation of the Village Head, BUM Desa managers, and community members involved in the BUM Desa program. Data analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results show that the governance of BUM Desa Jaya Makmur has fulfilled the principles of participation, policy coherence, reflexivity and adaptability, and democratic institutions. In addition, human resource development is carried out through skills training, empowerment of productive businesses, entrepreneurial mentoring, and increased community participation. These programs contribute to increasing community capacity, expanding business opportunities, increasing income, and strengthening village economic independence. The research findings confirm that good governance and sustainable human resource development are important factors in improving the performance of Village-Owned Enterprises and community welfare.